Pengaruh Online Trust dan Risk Perception Terhadap Online Purchase Intention Pada Pengguna E-Commerce di Kota Surabaya - Naufal Kurnia, Pandu Arkan; Widjaja , Fitri Novika; Ardiansyahmiraja, Bobby (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the influence of Online Trust on Risk Perception, Attitude, and Online Purchase Intention among e-commerce users in Surabaya City, using Structural Equation Modeling (SEM) with 160 respondents. Results show that Perceived Size and Perceived Reputation positively and significantly affect Online Trust. Online Trust significantly influences Attitude and Purchase Intention but has no effect on Risk Perception. Risk Perception does not influence Attitude or Purchase Intention. Attitude significantly affects Purchase Intention. These findings highlight Online Trust as a key driver of consumer attitudes and purchasing behavior in e-commerce, while Risk Perception plays a limited role.